Engineered Nickel Oxide Nanoparticle Causes Substantial Physicochemical Perturbation in Plants - Manna, Indrani; Bandyopadhyay, Maumita (Frontiers in Chemistry, 2017)
Concentration of engineered nickel oxide nanoparticle (NiO-NP) in nature is on the rise, owing to large scale industrial uses, which have accreted the scope of its exposure to plants, the primary producers of the ecosystem. Though an essential micronutrient for the animal system, supported by numerous studies confirming its toxicity at higher dosages, nickel oxide is graded as a human carcinogen by WHO. A few studies do depict toxicity and bioaccumulation of nickel in plants; however, interaction of NiO-NP with plants is not well-elucidated. It is known that exposure to NiO-NP can incite stress response, leading to cytotoxicity and growth retardation in some plants, but a defined work on the intricate physicochemical cellular responses and genotoxic challenges is wanting. The present study was planned to explore cytotoxicity of NiO-NP in the model plant, Allium cepa L., its internalization in the tissue and concomitant furore created in the antioxidant enzyme system of the plant. The prospect of the NiO-NP causing genotoxicity was also investigated. Detailed assessments biochemical profiles and genotoxicity potential of NiO-NP on A. cepa L. was performed and extended to four of its closest economically important relatives, Allium sativum L., Allium schoenoprasum L., Allium porrum L., and Allium fistulosum L. Growing root tips were treated with seven different concentrations of NiO-NP suspension (10–500 mg L−1), with deionised distilled water as negative control and 0.4 mM EMS solution as positive control. Study of genotoxic endpoints, like, mitotic indices (MI), chromosomal aberrations (CAs), and chromosome breaks confirmed NiO-NP induced genotoxicity in plants, even at a very low dose (10 mg L−1). That NiO-NP also perturbs biochemical homeostasis, disrupting normal physiology of the cell, was confirmed through changes in state of lipid peroxidation malonaldehyde (MDA), as well as, in oxidation marker enzymes, like catalase (CAT), super oxide dismutase (SOD), and guiacol peroxidase (POD) activities. It was evident that increase in NiO-NP concentration led to decrease in MIs in all the study materials, concomitant with a spike of stress-alleviating, antioxidant enzymes-CAT, POD, SOD, and significant increase in MDA formation. Hence, it can be confirmed that NiO-NP should be treated as an environmental hazard.